The effect of systemic hypertension on prostatic arterial hemodynamics in dogs with benign prostate hyperplasia - Çağatay ESİN (Kafkas Universitesi Veteriner Fakültesi Dergisi)
This study aimed to examine how systemic hypertension impacts resistance indices in the prostate artery by comparing ultrasonographic assessments of the prostate gland between normotensive and hypertensive dogs with benign prostatic hyperplasia (BPH). Dogs presenting with symptoms such as frequent urination, painful urination, and blood in the urine, and diagnosed with BPH, were divided into two groups: normotensive and hypertensive, with each group consisting of ten dogs. Blood pressure measurements, as well as B-mode and Doppler ultrasonographic evaluations, were conducted. The mean age for the normotensive and hypertensive groups were 9.80±1.81 and 11.10±1.79 years, respectively. The mean weight for the normotensive and hypertensive groups were 27.60±6.02 and 29.00±4.00 kg, respectively. The mean prostate volume for the normotensive and hypertensive groups were 22.35±2.76 and 22.78±2.35 years, respectively (P=0.708). Dogs with BPH who also had hypertension exhibited significantly higher resistive indices in the prostate arteries compared to those with BPH who were normotensive (P<0.001). While the RI value was 0.76±0.03 in BPH dogs with hypertension, the RI value was 0.62±0.05 in normotensive BPH dogs (P<0.001). Finally, in veterinary practice, when dealing with a hypertensive patient, it is important to consider potential risk factors for prostatic vascular dysfunction. Additionally, the possibility of clinically significant BPH in hypertensive patients should be considered, and appropriate diagnostic tests should be conducted.